SUSTAINABLE TOURISM VILLAGE DEVELOPMENT THROUGH STRENGTHENING COLLABORATIVE GOVERNANCE STRATEGY - Ratna Susanti,; Suci Purwandari,; Basnendar Herry Prilosadoso, (International Journal of Social Science, 2023)
development of tourism potential in Karangasem and Ngrombo Tourism Village. This research was conducted in a qualitative descriptive manner by elaborating the techniques of extracting data from in-depth interviews, observation, focus group discussions, and documentation to explore primary and secondary data. Checking the validity of the data has been done through triangulation of sources. The research subjects include elements of the government, private sector, axademics , mass media, communities, and local communities in Karangasem and Ngrombo Tourism Village. Meanwhile, the data analysis technique was compiled interactively including the stages of data collection, data reduction, data presentation, and concluding. Village-Owned Enterprises (BUMDes), academics, private sector, mass media, tourism awareness groups, youth organizations, and local communities. The collaborative governance process that occurs through face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes have made a positive contribution to increasing the acceleration of tourism potential development and promotion based on digital platforms from Karangasem and Ngrombo Tourism Villages. However, some challenges must be managed better in the aspect of building trust in the management of Karangasem and Ngrombo Tourism Village because there are different backgrounds and priority interests of each actor involved. In addition, long-term sustainable interventions need to be carried out on aspects of commitment to the process and shared understanding to have a multiplier effect on the outcome in the future. The results of this study are expected to provide real implications for the management of the Karangasem and Ngrombo Tourism Village and the Karangasem and Ngrombo Village Government to innovate in accelerating the promotion and commercialization of Karangasem and Ngrombo village tourism products.